Penerapan Positive Teaching Sebagai Langkah Awal Dalam Membangun Sekolah Positif Di Sekolah YLPI (Yayasan Lembaga Pendidikan Islam) - Herawaty, Yulia (UIR Press, 2022)
One critical factor students influence learning a better direction lies in qualified teachers. One indicator of teacher quality application is positive teaching. This study aims to which teachers in schools to implement positive teaching. The subjects in this study consisted of teachers SD, SMP and SMA at Pekanbaru Islamic Education Foundation (YLPI). This study used a simple random sampling technique with a total number of samples is 60 people. Data was collected using a positive teaching scale which has 8 component scales, a) attention, b) trust, c) respect for differences, d) goals, e) planning, f) motivation, g) expectations and h) contributions to the community. Data analysis used quantitative descriptive with percentage method. The results showed that the percentage of large, medium and low components was in the trust component as many as 12 people (20%), community contributions as many as 49 people (81,66%), and goals as many as 11 people (18,33%). And it is known that the application of positive schools through positive teaching is in the medium category, which is 73,33%.